Analisis Efektifitas Anggaran Modal Terhadap Pendapatan Usaha (Studi Kasus pada Seblak Prasmanan RC di Karawang) - Suhandoko, Alifia Rachma; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the impact of the capital budget on business income at Seblak Prasmanan RC in Karawang, West Java. The qualitative research method used is in-depth interviews which include business profile (history, initial capital), budgeting (funding sources, budget allocation, decision making process), business income (revenue trends, factors influencing income), and perceptions of effectiveness. budgeting of business income. Research finds that budgeting plays an important role in increasing business revenue. Effective budgeting can increase efficiency, increase production capacity, and increase competitiveness. Apart from that, other factors such as consistency of product quality and innovation also influence business income. In this research, Seblak Prasmanan RC in Karawang was chosen as the research subject because it meets the criteria and has quite large potential in developing the seblak business. It is hoped that the findings of this research can contribute to the development of the seblak industry in Indonesia and provide a reference for other entrepreneurs in managing their budgets effectively.